Minimizing perovskite solar cells' lead leakage with a cost‐effective and 160 days stable encapsulant - Haoxuan Liu; Can Li; Zongxu Zhang; Yating Shi; Fei Zhang (EcoMat)
Abstract Perovskite solar cells' (PSCs) potential lead leakage seriously threatens ecosystems and human health, significantly hindering their commercialization. In this paper, we develope a cost‐effective (less than 2$/m2) and long‐term stable SSP film by mixing sulfonated SiO2 with polyvinyl alcohol (PVA). Combined with polydimethylsiloxane (PDMS) forming the encapsulation layer, it can effectively prevent over 99% of lead leakage under simulated adverse weather conditions with different structures of devices (p‐i‐n and n‐i‐p) and modules. Even after 160 days of air storage, the film maintains excellent lead sequestration efficiency. Additionally, it has no negative impact on the performance and stability. This work offers a practical and economical strategy to mitigate the toxicity of perovskite photovoltaic devices, thereby promoting their commercialization.